Functional approaches to language - Bischoff, Shannon T.; Jany, Carmen, 1970- (Trends in linguistics. Studies and monographs ;, 2013)
Since the 1970s functionalism has been attached to a variety of movements and models making major contributions to linguistic theory. Over the past decades it has gained more ground, and we now have a substantial body of literature from various perspectives making a positive impact on the field of linguistics. This collection of papers brings leading scholars in this area together to provide recognition to the impact of functionalism on current linguistic theory highlighting its nature as a leading force within linguistics and beyond and defining its current and future directions.